Escapebody:: the paranoiac-critical method as dance practice - Barzagli Oliveira, Rafael; Roble, Odilon José (Revista Brasileira de Estudos da Presença, 2025)
This article discusses the reference to the paranoiac-critical method of Salvador Dalí, the notorious surrealist painter, for a contemporary dance practice. To this end, it develops an approach to the nexuses of intelligibility of the Tragic Philosophy, especially in the psychoanalytic solution, showing how unconscious motives, captured through events perceived in the body, can drive the dramaturgical construction in contemporary dance through a tragic myth based on the paranoiac-critical method, in this article, elucidating the event in the light of Achilles’ weeping in Homer’s Iliad.